107k views
0 votes
Consider the sequence of steps to solve the equation: 3(x − 4) + 5x = 9x − 36 Given ⇒ 3(x − 4) + 5x = 9x − 36 Step 1 ⇒ 3x − 12 + 5x = 9x − 36 Step 2 ⇒ 3x + 5x − 12 = 9x − 36 Step 3 ⇒ 8x − 12 = 9x − 36 Step 4 ⇒ 8x − 8x − 12 = 9x − 8x − 36 Step 5 ⇒ 0 − 12 = x − 36 Step 6 ⇒ −12 = x − 36 Step 7 ⇒ −12 + 36 = x − 36 + 36 Step 8 ⇒ 24 = x + 0 Step 9 ⇒ 24 = x Which property yields Step 7? A) Additive Inverse Property B) Additive Identity Property C) Addition Property of Equality D) Commutative Property of Addition

User Sanchia
by
4.9k points

2 Answers

4 votes

Answer:

c is the answer

Explanation:

User Fiore
by
5.9k points
3 votes

In Step 6, the equation is ...

-12 = x - 36

In step 7, the equation is ...

-12 +36 = x -36 +36

Clearly, to get to step 7, 36 has been added to both sides of the equation.

Adding 36 to both sides of the equation is justified by ...

... C) Addition Property of Equality

_____

More about the addition property of equality

The addition property of equality says you can add the same value to both sides of an equation without changing the values of the variables that make the equation true. Here, x=24 makes the equation of step 6 true, and x=24 makes the equation of step 7 true.

User StudioTime
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.